Optimalisasi Jenis Olahan Kering dan Cara Pengolahan Akhir Ketela - Harsojuwono, Bambang Admadi; Ngurah Agung, I Gusti; Pramana Mahardika, M. Surya (Jurnal Teknik Industri, 2011)
The research was aimed to determine the effect of the form of dry food products, and final processing of sweet potatoand their interaction, on the nutrition content, resistant starch of the products, and the increasing level of blood glucoseof mice after consuming the products. The method of the research was based on the completed random design with thefactorial experiment two factors were experimented, the first factor was the form of dry food products with four kinds of theproduct from namely: crispy, chip, cracker and snack. The second factor was final processing with two kinds of methodswere experiment was done using so nice which divided into eight blocks of combination treatments of the experiments. The crispy form of dry sweet potato product and final processed by oven roasting was the best product which could suppress the increasing level of blood glucose of mice to 8 mg/L and has resistant starch of about 39.29%. This product also had the best nutrition content such as content of protein, lipid, total sugar and starch of about 3.42%, 1.79%, 7.98%, and 50.02%.